Heavy metal content of Pb and Cd in bandik grouper (Cephalopholis boenak) in Banten Bay, Indonesia - Endang Juniardi; Sulistiono Sulistiono; Sigid Hariyadi; Mohammad Mukhlis Kamal (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Banten Bay is a developing area that is used by various activities such as fishing ports, industry and hotels. Many activities in the coastal areas of Serang City and Cilegon Regency have a serious impact on the quality of waters and fishery resources along Banten Bay. This study aims to analyze and determine maximum tolerance limit for bandik grouper (C. boenak) meat and gills which are safe for consumption by adults and children. The study was conducted at six stations, namely Panjang Island and Pamujaan Besar Island during the period of May, June and July 2019. Measurement of heavy metal content on meat and gills carried out using Atomic Absorption Spectrophotometric (AAS). The content of Pb and Cd in water fluctuates. The metal content of Pb and Cd in the meat and gills of bandik grouper has exceeded the quality standards set by BPOM and FAO/WHO, and is classified as polluted mild to moderate Pb bioconcentration factor values in grouper meat ranged from 6.78-72.00 and Pb bioconcentration in grouper gills 32.86-762.61. The maximum weight of grouper meat that can be tolerated for consumption for adults is 3,5 kg/week and children 1.0 kg/week.